The Hilton head metabolism Diet The revolutionary New plan that teaches your body to burn off fatt-and keep it off permanently. - Miller, Peter M. (New York: Warner, 1984)
Despite an increasing interest in health, a growing number of people in this country are overweight. In this updated edition, Dr. Miller incorporates the newest scientific findings to teach readers how to lose weight permanently. Inlcudes all-new menu plans based on new foods and new research.
includes index
Keywords: DIETETIC -- FEEDING; NUTRITIONAL REGIMEN; METABOLISM